Hak Ingkar Pejabat Pembuat Akta Tanah (PPAT) Dalam Kewajiban Menjadi Saksi Pada Proses Penyidikan Ataupun Peradilan - Brahmanta, I Made Satria; Yusa, I Gede (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 02 (2022)DO - 10.24843/AC.2022.v07.i02.p12, 2022)
This paper aimed to find out the position of PPAT's right to deny and the legal impact of PPAT if revealing secrets, to find out the position of the PPAT right of denial in the investigation and court process, this research used statute approach, this research was a normative research. The results are, in the investigation stage, PPAT can choose to carry out one of the two obligations (the right to vote in carrying out one of the obligations). And in court proceedings, PPAT might exercise the right of denial after the reasons presented are approved by the judge, but in certain cases PPAT cannot exercise the right of refusal or carry out the obligation to keep secrets. The application of legal sanctions for a PPAT who intentionally discloses the secrets of the parties to the land registration deed made by him, then the PPAT can be sentenced or strict sanctions in the form of dishonorable dismissal. PPAT will be given a punishment or sanction and will be dismissed from his position dishonorably given from the Indonesian National Land Agency. For those who are proven to have made a mistake, the imposition of penalties on civil matters, legal sanctions that can be imposed on those who are proven guilty are the necessity to fulfill an achievement whose amount is in accordance with the loss of the injured party, but in criminal matters, the punishment given to the defendant is in the form of punishment.